MEDIA ULAR TANGGA QR CODE TERHADAP KEMAMPUAN BERPIKIR LOGIS PADA ANAK USIA 5-6 TAHUN - Aulia, Elita Resti; Maulidiyah, Eka Cahya; Fitric, Ruqoyyah; Mas’udah, Mas’udah (Institut Agama Hindu Negeri Gde Pudja Mataram, 2022)
The ability to think logically is one of the cognitive abilities of children that need to be developed from an early age. Improving logical thinking skills can be done using interesting media in the form of a game of snakes and ladders qr code. The use of media combined with qr code technology can attract interest and motivate children in learning activities. The purpose of this study was to examine whether or not there is an influence of the qr code snake and ladder media on the logical thinking ability of children in the TK B group aged 5-6 years in Mantewe District. This study uses a quantitative approach with a quasi-experimental research design with a non-equivalent control group design. Data collection techniques using observation techniques with observation sheets. The research subjects were the children of group B in Pembina State Kindergarten, Mantewe Subdistrict with 40 samples consisting of an experimental group of 20 children and a control group of 20 children. Parametric statistical analysis technique using paired sample t-test. After the treatment of the snake and ladder game qr code, the results obtained a significant value in the pre-test and post-test of the experimental group of 0.000 <0.05. Then it can be stated that H0 is rejected and Ha is accepted, meaning that there is a difference between the child's logical thinking ability before the qr code snake and ladder game media is applied and the child's logical thinking ability after the qr code snake ladder game media is applied. Furthermore, it is hoped that this research can be used by teachers and can contribute especially in improving the logical thinking ability of early childhood.